BRICS+ v primežu sodobnih geopolitičnih in geoekonomskih paradigem - Žbogar, Tomaž (Vojaškošolski zbornik, 2024)
This paper discusses the rise and expansion of the BRICS+ group, focusing on its role in reforming global governance and establishing a multipolar world which, in its view, more fairly reflects the diverse interests and powers at the global level. The paper highlights how BRICS+ transcends economic cooperation, increasingly establishing itself as a key political and security actor striving to restructure international relations. There is an emphasis on the opposition to liberal unipolarity and Western hegemony in order to strengthen the autonomy and influence of the countries of the Global South. In addition to the geopolitical and economic aspects, the paper addresses innovations in the financial sector introduced by BRICS+, including the establishment of the New Development Bank and initiatives for de-dollarization, which aim to reduce dependence on the US dollar in international financial transactions. There are challenges within the BRICS+ group, however, such as coordinating national policies and maintaining internal cohesion, which are crucial for maintaining the group's long-term success and influence.
Keywords: BRICS+; dedolarizacija; de-dollarization; geopolitical dynamics; geopolitična dinamika; global governance; globalno upravljanje; Mednarodne organizacije; Mednarodni gospodarski odnosi; Mednarodni odnosi; multipolar world; multipolarni svet; ofenzivni realizem; offensive realism